Post-2015: what can the European Union learn from past international negotiations? - Niels Keijzer; Adam Moe Fejerskov (Deutsches Institut für Entwicklungspolitik (DIE), 2013)
On 27 February 2013 the European Commissioners for Development and Environment presented a proposal for a joint European Union (EU) position for a post-2015 framework on global development. This Briefing Paper looks into what the EU can learn from three past international negotiation processes on how to further develop and effectively promote a joint position: The 2008 Accra High Level Forum on Aid Effectiveness The 2011 Busan High Level Forum on Aid Effectiveness The 2012 Rio Conference on Sustainable Development The analysis shows that the influence of the EU is significantly reduced when individual Member States distance themselves from previously agreed joint EU positions. This is not to say that the EU can push things on its own, but rather that unity in the EU's positions and negotiation strategies – i.e. 27 states, each with their own wide-ranging views and interests – is key to convincing others that it would be worthwhile for them to align themselves with the EU's views and ideas. Five lessons are identified that could inform the EU's preparation and negotiation actions: Prepare well and complete on time: the approach to preparing EU positions has become heavier and more time-consuming, increasing the risk that a joint position could be adopted at a time when the draft outcome document is already at an advanced stage. Keep things flexible: a too detailed position can hamper the EU's flexibility (or reduce the usefulness of the position) in the case of unforeseen circumstances or strong shifts in the negotiation positions of other countries. The need for coordination between negotiations on the post-2015 development agenda and the Sustainable Development Goals (SDGs) – and their full integration, as desired by the EU – definitely calls for such flexibility. Seek broad-based alliances: the EU needs to strongly invest in seeking support from other United Nations (UN) members around key elements of its joint position if it is to negotiate successfully during the coming months. Promote a broad agenda: compared to environmental policy negotiations, development cooperation negotiations show stronger tendencies of EU Member States operating on their own or in likeminded coalitions. The potential inclusion of Sustainable Development Goals into the post-2015 framework may reduce that risk. EU coordination during Rio+20 presented some ideas on how the EU could organise itself. Convince with action, not with words: in negotiations the EU has developed a reputation of “do what I say and not what I do”. Given the possible greater focus of a post-2015 development agenda on areas and actions beyond development assistance, the importance of results in making policy areas such as trade and environment more development-friendly only increases.
Keywords: 330; Armut und Ungleichheit; Deutsche + Europäische + multilaterale Entwicklungspolitik